Severe Concomitant Injury Complicated by Heart Valvular Apparatus Damage - V. N Yakovlev; D. I. Levikov; Yu. V. Marchenkov; D. V. Shumakov; P. N Goncharov; A. M, Kuznetsov; V. N. Poptsov; M. K. Rybakova; I. O. Molochnikov; N. G. Neznamova; M. V. Savchenko; V. L. Shaibakova (Общая реаниматология, 2012)
The paper describes a rare case of successful surgical treatment for mitral insufficiency due to heart valvular apparatus damage in the acute period of severe concomitant injury. Prosthetic mitral valve replacement was done on day 3 after injury. The patient was switched to spontaneous breathing on day 7 postoperatively and transferred to a surgical unit on day 11. Timely diagnosis, a comprehensive therapeutic approach, active surgical policy, the availability of up-to-date medical equipment, and the presence of high-quality physicians allowed severe cardiopulmonary insufficiency to be eliminated and the patient was discharged from hospital in a satisfactory state on day 25 after injury. Key words: severe concomitant injury, blunt chest injury, mitral valve damage, cardiac surgery.